GERAKAN ORGANISASI BERBASIS KEAGAMAAN MELAWAN HIV/AIDS DI INDONESIA: PENILAIAN PADA WILAYAH JAWA TENGAH DAN BALI - Anna Marie Wattie; Nono S. A. Sumampouw (IAIN Manado, 2018)
Abstract. This article aims to understand the approach used by Faith Based Organization (FBO) in the tackling and handling program of HIV and AIDS, in relation to the prevention, infection, as well as the treatment in social-cultural perspective. The data collecting is done through profound interview and observation in two research areas: North-Beach Areas (Pantai Utara), Central Java and Denpasar, Bali. Both locus were chosen and compared based on the differences in socio-cultural formation, particularly in the religious background majority which in control of the social life. It is found that the involvement of both the institution and religious leaders in the countermeasures of HIV and AIDS has a strategical value either directly or indirectly. The involvement of religious organizations in these two areas, even though differ in effectiveness, scale of implementation, problems encountered, value approach, intervention and organizational attachment, and the social-cultural construction of the society has adduced changes in discourse and practices related to the HIV and AIDS issues, either in the circle of the religious leaders and the community in general. The North-Beach area in Central Java which only for the past five years go through with the countermeasures program of HIV and AIDS formally, structurally, direct, and organizational by FBO in this case Nahdlatul Ulama (NU), has the effectivity and acceptance for different people and slower that what has happened in Bali, where the FBO tends to be involved through non-organizational network.Keywords: HIV, AIDS, ODHA, Religion, Moslem, Hindu-Bali, FBO, NU, BanjarAbstrak. Artikel ini bertujuan memahami pendekatan yang dilakukan Lembaga Berbasis Keagamaan atau Faith Based Organization (FBO) dalam program penanggulangan dan penanganan HIV dan AIDS, baik terkait dengan pencegahan, penularan maupun perawatan dalam perspektif sosial-budaya. Pengumpulan data dilakukan lewat wawancara mendalam dan observasi di dua wilayah penelitian, yaitu: daerah Pantai Utara, Jawa Tengah dan Denpasar, Bali. Kedua lokus dipilih dan dibandingkan dengan alasan memiliki formasi sosio-kultural berbeda terutama dalam latar belakang agama mayoritas penduduk yang mengatur kehidupan bermasyarakat. Ditemukan bahwa pelibatan lembaga dan tokoh keagamaan dalam penanggulangan HIV dan AIDS punya nilai strategis, baik secara langsung maupun tidak langsung. Pelibatan organisasi keagamaan di dua daerah ini, sekalipun berbeda dalam hal efektifitas, skala pelaksanaan, masalah yang dihadapi, pendekatan nilai, intervensi dan keterikatan organisasional serta konstruksi sosial-budaya masyarakat telah menunjukkan adanya perubahan wacana dan praktek terkait dengan isu HIV dan AIDS, baik di kalangan pemuka agama dan masyarakat luas. Daerah Pantai Utara Jawa Tengah yang kurang-lebih baru saja lima tahun melaksanakan program penanganan HIV dan AIDS secara formal, struktural, langsung dan organisasional oleh FBO dalam hal ini Nahdlatul Ulama (NU), memiliki efektifitas dan penerimaan di kalangan masyarakat yang berbeda serta lebih lambat daripada yang terjadi di Bali, dimana FBO cenderung dilibatkan lewat jejarang non-organisasional.Kata Kunci: HIV, AIDS, ODHA, Agama, Islam, Hindu-Bali, FBO, NU, Banjar